Joshua J. answered • 03/17/21

I’m a student who excels in classes and wants to help others

2C+3T=$23

6C+5T=$43

C=chairs

T=Tables

The first step

in this equation is to determine one variable so that we can plug it in to find the other. HERE, we will find C first

This is done by multiplying the top equation by -3 so that the C’s cancel out. This gives us:

-6c-9t=-69

6c+5T=43 (do not touch this equation)

now we can cancel out the C variable and get the base equation of -4t=-26

telling us each table costs $6.5 after we divide by 4.

now we plug (6.5) into either equation to find out C